A contribution to the analysis and developing of the system for the automatic calculating of the vital machine elements - Gatalo, Ratko; Komarica, Novko; Zeljković, Milan; Borojev, Ljubomir; Novaković, Dragoljub; Kovačević, Sava (Journal of Production Engineering, 1993)
In the paper the original researching results in the area of the machine tool vital elements calculating are given. These researching are realized in the Laboratory for Machine Tools of the Institute for Production Engineering of Novi Sad. In the first part of the paper an attempt was made to systematize the existing methods of analysis and calculating for typical machine elements and the targets which are realized by this methods. For this systematization the grafical plane and space reviews also are given. For the previous results of the methods and targets the characteristics some of the typical software packages and systems for automatic cal¬culating and analysis are systematized. In the second part of the paper some developing results of the software systems for automatic calculating and analysis, which are developed in the Laboratory for Machine Tools, are given. These sys-tems are: SAPOR-P - system for automatic modeling and caculating of the axial structures, NOSEL - system for automatic design and analysis of the prismatic carrying elements, ZUPCAN - system for auto¬matic gear design and RADHIL - system for automatic calculating and analysis of the hydrostatic bearings behavior. For all of these systems the concept, the solution of the processor and some output results also are given.